2021
DOI: 10.32677/ijcr.v7i10.3086
|View full text |Cite
|
Sign up to set email alerts
|

Unmasking of miliary tuberculosis in COVID-19: A case report

Abstract: Both coronavirus disease-19 (COVID-19) and pulmonary tuberculosis (PTB) are transmitted through the respiratory route and are related to various risk factors. The index case was a 45-year-old female who presented to a tertiary care hospital in North India with complaints of dry cough, loss of weight, and appetite for twenty days followed by fever and dyspnea for five days. RT-PCR for COVID-19 turned out positive. Chest-roentgenogram revealed bilateral homogenous micronodules. She was started on COVID-19 treatm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…Then, the remaining 2337 studies were screened by title and abstract. Full-text screening was conducted for 23 studies, and finally, data were extracted from 21 studies comprising [11][12][13][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36] 33 individual cases (Fig 1). The studies were reported from 13 countries with the highest frequency from the United States of America (10 patients), and Tu ¨rkiye (eight patients) followed by Bangladesh (three patients), and Mexico (three patients).…”
Section: Resultsmentioning
confidence: 99%
“…Then, the remaining 2337 studies were screened by title and abstract. Full-text screening was conducted for 23 studies, and finally, data were extracted from 21 studies comprising [11][12][13][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36] 33 individual cases (Fig 1). The studies were reported from 13 countries with the highest frequency from the United States of America (10 patients), and Tu ¨rkiye (eight patients) followed by Bangladesh (three patients), and Mexico (three patients).…”
Section: Resultsmentioning
confidence: 99%